Neuron‐microglia interaction induced bi‐directional cytotoxicity associated with calpain activation. Issue 3 (18th October 2016) - Podbielska, Maria; Das, Arabinda; Smith, Amena W.; Chauhan, Ashok; Ray, Swapan K.; Inoue, Jun; Azuma, Mitsuyoshi; Nozaki, Kenkichi; Hogan, Edward L.; Banik, Naren L.
Abstract: Activated microglia release pro‐inflammatory factors and calpain into the extracellular milieu, damaging surrounding neurons. However, mechanistic links to progressive neurodegeneration in disease such as multiple sclerosis (MS) remain obscure. We hypothesize that persistent damaged/dying neurons may also release cytotoxic factors and calpain into the media, which then activate microglia again. Thus, inflammation, neuronal damage, and microglia activation, i.e., bi‐directional interaction between neurons and microglia, may be involved in the progressive neurodegeneration. We tested this hypothesis using two in vitro models: (i) the effects of soluble factors from damaged primary cortical neurons upon primary rat neurons and microglia and (ii) soluble factors released from CD3/CD28 activated peripheral blood mononuclear cells of MS patients on primary human neurons and microglia. The first model indicated that neurons due to injury with pro‐inflammatory agents (IFN‐γ) release soluble neurotoxic factors, including COX‐2, reactive oxygen species, and calpain, thus activating microglia, which in turn released neurotoxic factors as well. This repeated microglial activation leads to persistent inflammation and neurodegeneration. The released calpain from neurons and microglia was confirmed by the use of calpain inhibitor calpeptin or SNJ‐1945 as well as μ‐ and m‐calpain knock down using the small interfering RNA (siRNA) technology. Our second model using activated peripheral blood mononuclear cells, a source of pro‐inflammatory Th1/Th17 cytokines and calpain released from auto‐reactive T cells, corroborated similar results in human primary cell cultures and confirmed calpain to be involved in progressive MS. These insights into reciprocal paracrine regulation of cell injury and calpain activation in the progressive phase of MS, Parkinson's disease, and other neurodegenerative diseases suggest potentially beneficial preventive and therapeutic strategies, including calpain inhibition. Abstract : Inflammation, neuronal damage, and microglia activation, i.e., bi‐directional interaction between neurons and microglia, may be involved in neurodegenerative disease mechanisms. This study used two in vitro models to advance our understanding of the pathogenesis: (1) the effects of soluble factors from the damaged primary cortical neurons upon primary rat neurons and microglia and (2) soluble factors released from the CD3/CD28 activated peripheral blood mononuclear cells (PBMCsAct ) from multiple sclerosis (MS) patients on primary human neurons and microglia. Our results indicate that neurons injured with pro‐inflammatory agents (e.g., IFN‐γ) release soluble neurotoxic factors, including COX‐2, reactive oxygen species (ROS), and calpain, that activate microglia, which in turn release neurotoxic factors to perpetuate the bi‐directional cytotoxicity.